Oxidative stress responses to a graded maximal exercise test in older adults following explosive-type resistance training - Ceci, Roberta; Beltran Valls, Maria Reyes; Duranti, Guglielmo; Dimauro, Ivan; Quaranta, Federico; Pittaluga, Monica; Sabatini, Stefania; Caserotti, Paolo; Parisi, Paolo; Parisi, Attilio; Caporossi, Daniela (Redox biology, 2014)
We recently demonstrated that low frequency, moderate intensity, explosive-type resistance training (EMRT) is highly beneficial in elderly subjects towards muscle strength and power, with a systemic adaptive response of anti-oxidant and stress-induced markers. In the present study, we aimed to evaluate the impact of EMRT on oxidative stress biomarkers induced in old people (70-75 years) by a single bout of acute, intense exercise. Sixteen subjects randomly assigned to either a control, not exercising group (n=8) or a trained group performing EMRT protocol for 12-weeks (n=8), were submitted to a graded maximal exercise stress test (GXT) at baseline and after the 12-weeks of EMRT protocol, with blood samples collected before, immediately after, 1 and 24h post-GXT test. Blood glutathione (GSH, GSSG, GSH/GSSG), plasma malonaldehyde (MDA), protein carbonyls and creatine kinase (CK) levels, as well as PBMCs cellular damage (Comet assay, apoptosis) and stress-protein response (Hsp70 and Hsp27 expression) were evaluated. The use of multiple biomarkers allowed us to confirm that EMRT per se neither affected redox homeostasis nor induced any cellular and oxidative damage. Following the GXT, the EMRT group displayed a higher GSH/GSSG ratio and a less pronounced increase in MDA, protein carbonyls and CK levels compared to control group. Moreover, we found that Hsp70 and Hsp27 proteins were induced after GXT only in EMRT group, while any significant modification within 24h was detected in untrained group. Apoptosis rates and DNA damage did not show any significant variation in relation to EMRT and/or GXT. In conclusion, the adherence to an EMRT protocol is able to induce a cellular adaptation allowing healthy elderly trained subjects to cope with the oxidative stress induced by an acute exercise more effectively than the aged-matched sedentary subjects.